ECG patch monitor: a telemedicine system for remote monitoring and assisting patients during a heart attack. (28th May 2020) - Charrad, Tesnim; Nouira, Kaouther; Ferchichi, Ahmed
This paper deals with real-time ubiquitous healthcare monitoring systems. The goal is not just to supply a medical service in hospitals and medical offices, but also to provide a reliable service during the normal daily life. In this purpose, a monitoring system for patients suffering from heart disease is designed. This system is called 'ECG patch monitor' which enables cardiac data collection and analysis in real-world environments such as at work or at home. It is an adhesive device attached directly to the skin. ECG patch monitor aims to prevent heart attacks or any other form of heart failure. It uses a real-time anomaly detection algorithm. Once an anomaly is detected, the device alerts the healthcare centre. ECG patch monitor is remotely controlled by the healthcare centre through a platform. The ECG patch monitor allows doctors to call the patient in emergency to verify his health condition. In the extreme case, the doctor can remotely perform an electroshock or a drug injection. The doctor can locate the patient and send an ambulance.